Getting clues from nature: the impact of grass hay on suckling piglets’ gastrointestinal growth and colonic microbiota - Yao, Renjie; Cools, An; van Hees, Hubèrt M. J.; Chiers, Koen; Mebratu, Awot Teklu; Aluwé, Marijke; Maes, Dominiek; Janssens, Geert P. J. (Frontiers in Cellular and Infection Microbiology, 2024)
Introduction The effect of dietary fiber on pig production has been extensively evaluated. Inspired by observations of the diet of wild, young piglets, this study aimed to examine the possibility of feeding grass hay to suckling piglets besides concentrated creep feed. Methods The sow-nursed piglets in this study were divided into two groups based on balanced sow parities. The control group (CON, n = 7 sows) only received a regular, concentrated creep feed, while the treatment piglets (GH, n = 8 sows) were also provided with chopped grass hay from 2 days of age until weaning (28 days). At weaning, one piglet with a median weight was selected from each litter for post-mortem evaluation. Subsequently, six pigs around median weight per sow were grouped into nursery pens and monitored for their feed intake and body weight gain until 9 weeks of age. Results and discussion Piglets in GH consumed, on average, 57 g of grass hay per piglet during the entire lactation period. The emptied weight of the small and large intestine was significantly greater in GH (280 vs. 228 g, 88.8 vs. 79.3 g, respectively, p < 0.05), and the length of the large intestine was stimulated by the grass hay (164 vs. 150 cm, p < 0.05). Morphologically, the villus height in the jejunum was higher in GH (p < 0.05). In the large intestine, the crypt depth of the mid-colon was lower in GH. Moreover, the short-chain fatty acid (SCFA) concentrations in the cecum were increased in GH compared to CON (1,179 vs. 948 µmol/g dry matter, p < 0.05), whereas in the colon, SCFA concentrations were lower in CON (341 vs. 278 µmol/g dry matter, p < 0.05). There was no major impact of grass hay inclusion on the colonic microbiota composition. Only a trend was observed for a lower inverse of the classical Simpson (InvSimpon) index and a higher abundance of Lactobacillus genera in GH. After weaning, no significant differences in feed intake and body weight gain were observed. In conclusion, supplementing the grass hay to suckling piglets led to alterations in intestinal morphology, increased SCFA fermentation in proximal sections of large intestine, stimulation of gastrointestinal tract growth, and subtle modifications in colonic microbiota.